Strengthening rock analysis skills through petrology and petrography training for vocational school students majoring in Geology and Mining Engineering, Makassar City - Farida, Meutia; Irfan, Ulva Ria; Maulana, Adi; Sirajuddin, Haerany; Alimuddin, Ilham; Umar, Hamid; Thamrin, Meinarni; ., Sahabuddin; ., Maulana; Ikhwana, Nur; Asfar, Suryawan (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Over the last 2 decades, the need for the application of geosciences has become increasingly in society, geological natural disasters have made various levels of society aware of the importance of knowledge and understanding of the geological conditions of the Indonesian Archipelago. One of the impacts is the increasing number of vocational schools and universities providing earth education. Therefore, a curriculum that includes "Earth Science" as part of its subjects is needed. Vocational High School (SMK) Applied Techno Aviation, Department of Geological and Mining Engineering, Makassar City produces employees who are ready to be deployed in the field to work as technicians, so adequate skills are required in rock identification. Therefore, this training aims to improve students' skills as initial in improving the quality of their introduction to minerals and rocks. The results of this training show a positive trend in student test results by 5% - 27% improving and strengthening student skills, especially in petrology and petrography, is necessary to develop student quality.